PENGOBATAN TRADISIONAL (BAKERA) DI DESA TALENGAN KECAMATAN TABUKAN TENGAH KABUPATEN KEPULAUAN SANGIHE - Mangamba, Claudia; Pratiknjo, Maria Heny; Matheosz, Jenny Nelly (Universitas Sam Ratulangi, 2020)
Every ethnic tribe in Indonesia has a distinctive culture that is different from each other. Each culture also has various aspects that contain knowledge and guidelines and life procedures that are invaluable. One such aspect is traditional medicine.One of the Ethnic Groups in Indonesia who still have Knowledge of Traditional Medicine is the Sangihe tribe in Talengen village Tabukan Tengah district of Kepulauan Sangihe Regency of North Sulawesi Province they still maintain, and still rely on traditional medicine either in the form of potions, especially in women after childbirth or the period of sedation. People strongly believe that by means of traditional medicine bakera this disease can be cured quickly and has no side effects.Traditional Bakera Medicine, as a healer revitalizes the weakened body after childbirth, caring for the skin and also the female organs. In addition, bakera treatment also has the meaning of brotherhood because, during the treatment process bakera takes place close relatives come together just to encourage mothers who are doing bakera treatmentTraditional medicine is often regarded as irrational, no size and full of superstitions. It is decreasing public knowledge about traditional medicine bakera, because of the absence of the older generation in providing teachings or writings that support for the preservation of the tradition. Shifts triggered by intensive interactions with the outside world due to urbanization as well as educational factorsKeywords: traditional medicine, bakera, Sangihe